CKD-506: A novel HDAC6-selective inhibitor that exerts therapeutic effects in a rodent model of multiple sclerosis - Daekwon Bae (Nature Portfolio, 2021)
Abstract Despite advances in therapeutic strategies for multiple sclerosis (MS), the therapy options remain limited with various adverse effects. Here, the therapeutic potential of CKD-506, a novel HDAC6-selective inhibitor, against MS was evaluated in mice with myelin oligodendrocyte glycoprotein35–55 (MOG35–55)-induced experimental autoimmune encephalitis (EAE) under various treatment regimens. CKD-506 exerted prophylactic and therapeutic effects by regulating peripheral immune responses and maintaining blood–brain barrier (BBB) integrity. In MOG35–55-re-stimulated splenocytes, CKD-506 decreased proliferation and downregulated the expression of IFN-γ and IL-17A. CKD-506 downregulated the levels of pro-inflammatory cytokines in the blood of EAE mice. Additionally, CKD-506 decreased the leakage of intravenously administered Evans blue into the spinal cord; CD4+ T cells and CD4−CD11b+CD45+ macrophage/microglia in the spinal cord was also decreased. Moreover, CKD-506 exhibited therapeutic efficacy against MS, even when drug administration was discontinued from day 15 post-EAE induction. Disease exacerbation was not observed when fingolimod was changed to CKD-506 from day 15 post-EAE induction. CKD-506 alleviated depression-like behavior at the pre-symptomatic stage of EAE. In conclusion, CKD-506 exerts therapeutic effects by regulating T cell- and macrophage-mediated peripheral immune responses and strengthening BBB integrity. Our results suggest that CKD-506 is a potential therapeutic agent for MS.